Impact of Rural and Urban Electricity Access on Economic Growth in Zimbabwe - Mhaka, Simbarashe; Runganga, Raynold; Nyagweta, David T.; Kaseke, Nyasha; Mishi, Syden (International Journal of Energy Economics and Policy, 2020)
Lack of access to reliable electricity to both rural and urban Zimbabweans is negatively affecting the quality of people’s life. The country has been experiencing extended hours of load shedding which result in the population having more hours without electricity per day than with electricity. Access to electricity complimented by droughts, natural disasters has impacted on production activities for the people hence causing poverty to many. The study used time series data for the period 1992-2018. The Dynamic Ordinary Least Squares (DOLS) was used as the main model of assess electricity access on economic growth. The results reveals that electricity access to urban population and electricity access to population (EAP) have positive significant impact on economic growth. However, electricity access to rural population was found to be statistically insignificant reflecting that electricity is not always available when it is needed in the rural areas. The study recommends that there is need to improve electricity access for both urban and rural population through on-grid and off-grid systems and expanded electricity generation to meet demand. This will improve socio-economic activities people would be able to carry out productive activities such as irrigation, processing and manufacturing or value addition of certain agriculture out. Keywords: Urban electricity access, rural electricity access, Economic Growth. JEL Classifications: C32, R11, E24 DOI: https://doi.org/10.32479/ijeep.10141